Bibliotecas digitais em Arquitetura e urbanismo: um estudo sobre a arquitetura da informação digital - Fantinel, Rosemary Gay (2009)
The goal of this paper was to search the state of the art from the Digital Libraries in Architecture and Urbanism in the Higher Education Institutions (IES) through conceptualizations and showing the importance of Digital Libraries in the disclosure and easing of information transferring. Questions about digital information architecture, usability, digital preservation and accessibility were approached. The research was made in the websites of Brazilian Universities, firstly to identify the institutions which offered the Architecture and Urbanism course, focusing on postgraduate education. After identifying the offering, the research was done by analyzing the contents, storage and dissemination and access to information, these libraries. It was found that the digital libraries are increasingly and taking part of organizations and educational institutions focusing on the knowledge dissemination releasing digitally information that may be needed for institution or the individual. A monitoring was done over of the physical and computational restructuring of the Board of Studies and Research in Architecture and Urbanism (Câmara de Estudos e Pesquisa em Arquitetura e Urbanismo, CEPAU), from the Architecture and Urbanism Course of the Federal University of Rio Grande do Norte (UFRN), showing the need of installing a Digital Library to integrate the databases of PPGAU s research groups, which today remain independent, with no interface among themselves. The research chosen area was Architecture and Urbanism, because there is a gap and little documentation about digital libraries in this area